Transcatheter Closure of Atrial Septal Defect with Amplatzer Septal Occluder in Adults: Immediate, Short, and Intermediate-Term Results - Mostafa Behjati (Journal of Tehran University Heart Center, 2011)
Background: The transcatheter closure of the atrial septal defect (ASD) has become an alternative technique to surgical procedures. The aim of this study was to assess the immediate, short, and intermediate-term results of the transcatheter closure of the secundum ASD with the Amplatzer Septal Occluder (ASO) in adult Iranian patients.